Identifikasi Struktur Patahan Daerah Panas Bumi Gunung Tampomas Berdasarkan Derivative Analysis dan Forward Modelling 2.5D dengan Metode Gravitasi - Sultan Ahmad Syarifuddin; Suharsono Suharsono; Iqbal Takodama (Jurnal Geologi dan Sumberdaya Mineral, 2026)
The Mount Tampomas Geothermal Area is located in Sumedang Regency, West Java Province. This study aims to interpret the distribution of subsurface fault structures based on gravity data analysis over an area of 14 × 14 km². Residual gravity anomaly analysis reveals the presence of a low gravity anomaly in the central part of the volcanic edifice, which is interpreted as a low-density zone associated with a magma ascent pathway within the volcanic system. The results of derivative analysis, correlated with surface geological data, indicate the presence of fault structures comprising normal faults, strike-slip faults, and reverse faults, which represent structural patterns predominantly controlled by volcanic activity. Forward modelling applied to several profiles yields the subsurface lithological density distribution, including the Subang Formation (2.40 g/cm³), Kaliwangu Formation (2.35 g/cm³), old volcanic lahar breccia (2.85 g/cm³), undifferentiated volcaniclastic tuffaceous sand (2.55 g/cm³), pumiceous tuff (2.60 g/cm³), breccia and agglomerate (2.70 g/cm³), and young volcanic lava (2.50 g/cm³).The results of this study provide a preliminary characterization of subsurface fault structures in the Mount Tampomas Geothermal Area based on gravity methods. Keywords : Gravity, Geothermal, Tampomas, Derivative Analysis, Forward Modelling